2016
DOI: 10.1680/jgele.15.00176
|View full text |Cite
|
Sign up to set email alerts
|

Critical state interpretation of effects of fines in silty sands

Abstract: The effect of the fines content in silty sands on the location of the critical state line (CSL) has been investigated by performing standard drained and undrained triaxial tests on reconstituted samples containing Sydney sand, feldspar fines and mixtures of the two at 20, 40 and 60% fines content. In the e-log p′ plane, CSLs of silt–sand mixtures shifted parallel to one another. The transitional fines content of silt–sand mixtures was 40%. Transitional soil behaviour was also observed in silt–sand samples that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 17 publications
0
6
1
1
Order By: Relevance
“…It has been previously suggested that the transitional behaviour is due to different reasons such as fines content [19] or fabric structure [12]. However, the findings of this study show that although these factors affect the location of the CSL, the initial void ratio strongly influences transitional behaviour.…”
Section: Resultscontrasting
confidence: 67%
See 2 more Smart Citations
“…It has been previously suggested that the transitional behaviour is due to different reasons such as fines content [19] or fabric structure [12]. However, the findings of this study show that although these factors affect the location of the CSL, the initial void ratio strongly influences transitional behaviour.…”
Section: Resultscontrasting
confidence: 67%
“…Recent studies [10,8,[11][12][13] on intermediate soils reported that soils with a mixture of particles ranging between sand and clay that were remoulded in laboratory conditions did not approach a unique critical state line (CSL). Shipton and Coop [10] showed that each type of soil produced a wide range of CSLs, and the authors proposed that these lines are influenced by the presence of fine particles within the soil mass.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kwa and Airey [15] determined the effect of the addition of non-plastic feldspar particles (<0.075 mm) on the properties of quartzite sand. The authors performed tests on samples of well-grained, fully saturated soils, compacted with the standard Proctor method (at optimum water content) and minimally compacted, to determine the effect of fine particles on the location of the critical state line (CSL) on the e-log p .…”
Section: Introductionmentioning
confidence: 99%
“…Bedin et al [14] and Carrera et al [23] successfully investigated the behaviour of gold or Stava tailings within the critical state framework. Under this framework, the effects of finer particles, i.e., silts on sands behaviour, have been analyzed [24][25][26][27]. It can be seen that the fly ash is normally employed as additive and to be mixed with soils with poor geotechnical characteristics for the purpose of improving their mechanical properties.…”
Section: Introductionmentioning
confidence: 99%